CHEMICAL ELEMENTS DIFFUSION IN THE SOLAR INTERIOR - Ali, H S (Al-Nahrain Journal of Science, 2018)
The standard solar model and equation of state have been used to study relative diffusion ofHydrogen and Helium in the present time for solar interior, as a function of distance and depth fromthe center of the star. The effects of temperature and density on diffusion velocity for thesechemical elements have been explaned.It is found that heat flow which is arising from these reactions leads to an increase in heliumdiffusion velocity, while the temperature and density leading to a decrease in Hydrogen diffusionvelocity. This means that Hydrogen behaves inversely with that for helium does through thesereactions. Accordingly, diffusion percentages for Hydrogen, Helium and other Heavy Elementscould be determined for the main sequence stars and white dwarf stars.